A narrative future for Europe–China economic relations after the financial crisis. Issue 1 (March 2016) - Zhang, Zhan
This article provides a detailed comparative analysis of how leading European media outlets—three elite newspapers from the United Kingdom, France, and Germany—reported economic news as it related to China from 2008, the beginning of the global financial crisis, until 2014. It illustrates the changing nature of European media perceptions of China and a growing interdependence between Europe and China after the financial crisis. Media messages directed toward domestic audiences and global stakeholders shaped public perceptions and influenced political, economic, and diplomatic narratives. In addition to a general increase in attention to news focused on China's economy after the financial crisis, the three European newspapers also shared essentially the same news frames when they reported economic news about China. Some differences were noted, however, as the British and German newspapers focused on their domestic interests with China's economy while the French newspaper preferred to discuss issues from the perspective of the European Union. All three newspapers were attentive to the pace of China's rise and to the problems and obstacles of doing business in China as well as to China's importance for Europe's future economic development. The news narratives were dominated by a tension between hope and uncertainty.